Impact of tawhidic paradigm in transforming human talent for sustainable performance among social enterprises - Sarif, Suhaimi Mhd (2017)
This study explores the effect of Tawhidic paradigm in transforming human talent for sustainable performance among social enterprises. Sosial enterprises are unique business entities that combined business and social objectives. Tawhidic paradigm enables strong mindset, behavior and attitude towards enduring and sustaining the performance of social enterprises in Malaysia. The study used personal interview with social enterprises to solicit their views pertaining the impact of Tawhidic paradigm into various dimensions of social enterprises. The informants argued that the Index of Shariah Malaysia compliance, halal and Toyyiban standards have been the mechanism of implementing Tawhidic paradigm that are able to sustain business performance.